Unpacking power dynamics and women's economic empowerment in polygynous households in Burkina Faso - Eissler, Sarah; Heckert, Jessica; Pedehombga, Abdoulaye; Sanou, Armande; Ganaba, Rasmané; Gelli, Aulo (Wiley, 2025)
Objective We aim to describe power distributions in polygynous households and consider how these matter for the production and allocation of food-generating resources in western Burkina Faso, where there is a high prevalence of polygyny.